Quantitative survey of three hectares of "cerrado" (savanna) vegetation - Elias de Paula, José; Imaña-Encinas, José; Sugimoto, Nilton (Pesquisa Agropecuaria Brasileira, 1998)
A study was carried out in order to obtain a quantitative description of the vegetation covering three hectares of "cerrado" (savanna) located in the Marflora holdings, municipality of Santa Quitéria, State of Maranhão, Brazil. Descriptive parameters were obtained from 1,413 trees with diameter at breast-height (dbh) larger than 5.0 cm and distributed within 41 species. The data obtained included wood volume, basal area and quantity of dry wood for the main stem and branches for each area and for every species. Average wood volume and weight were 40.50 m3/ha and 31.63 t/ha, respectively. A total of 3,177 individuals with dbh smaller than 5.0 cm was accounted for the natural regeneration in the whole area.